Twelve-month analgesia and rescue, by cooled radiofrequency ablation treatment of osteoarthritic knee pain: results from a prospective, multicenter, randomized, cross-over trial. Issue 4 (16th February 2019) - Davis, Tim; Loudermilk, Eric; DePalma, Michael; Hunter, Corey; Lindley, David A; Patel, Nileshkumar; Choi, Daniel; Soloman, Marc; Gupta, Anita; Desai, Mehul; Cook, Elizabeth; Kapural, Leonardo
Abstract : Background and objectives: As a follow-up to the 6-month report, 12 this study investigated the analgesic effect of cooled radiofrequency ablation (CRFA) in patients with knee osteoarthritis (OA) 12 months postintervention and its ability to provide pain relief in patients who experienced unsatisfactory effects of intra-articular steroid injection (IAS). Methods: Seventy-eight per cent (52/67) of patients originally treated with CRFA were evaluated at 12 months, while at 6 months post-IAS, 82% (58/71) of those patients crossed over to CRFA and assessed 6 months later. Results: At 12 months, 65% of the original CRFA group had pain reduction ≥50%, and the mean overall drop was 4.3 points (p<0.0001) on the numeric rating scale. Seventy-five per cent reported 'improved' effects. The cross-over group demonstrated improvements in pain and functional capacity (p<0.0001). No unanticipated adverse events occurred. Conclusions: This study demonstrates that analgesia following CRFA for OA knee pain could last for at least 12 months and could rescue patients who continue to experience intolerable discomfort following IAS. Clinical trial registration: The ClinicalTrials.gov registration number for this study is NCT02343003 .